Three-dimensional, mesoporous titanosilicates as catalysts for producing biodiesel and biolubricants - Kotwal, Mehejabeen; Kumar, Anuj; Darbha, Srinivas (Journal of Molecular Catalysis A-Chemical, 2013)
The application of three-dimensional, mesoporous titanosilicates, Ti-SBA-12 and Ti-SBA-16, as reusable solid acid catalysts for producing biodiesel and biolubricants is reported for the first time. Biodiesel was prepared by esterification of oleic acid with monohydric methanol and biolubricants by esterification with polyhydric alcohols (glycerol, trimethylolpropane, neopentyl glycol and pentaerythritol). High catalytic activity of these catalysts is attributed to the presence of dispersed Lewis acidic Ti sites and mesoporosity in the structure. Biodiesel yields as high as 90 mol% were obtained at 443 K. Surface hydrophobicity of the catalyst has also a predominant role, especially, in reactions involving polyhydric alcohols. In those reactions, Ti-SBA-16 showed higher catalytic activity than Ti-SBA-12. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Biodiesel; Esterification of fatty acid; Lubricant basestocks; mesoporous materials; Ti-SBA-12; Ti-SBA-16; Titanosilicates

Solid, double-metal cyanide catalysts for synthesis of hyperbranched polyesters and aliphatic polycarbonates - Sebastian, Joby; Darbha, Srinivas (Journal of Chemical Sciences, 2014)
Fe-Zn and Co-Zn double-metal cyanide (DMC) complexes exhibit highly efficient and selective catalytic activity for synthesis of hyperbranched polyesters (glycerol succinic acid (G-SA) and glycerol adipic acid (G-AA)) and aliphatic polycarbonates (via., alternative co-polymerization of cyclohexene oxide and CO2), respectively. The influence of method of preparation of DMC, in particular the mode of addition of reagents, on its physicochemical and catalytic properties was investigated. Co-Zn DMC was found highly selective for polycarbonate (than polyethers) formation. Catalysts prepared using tert-butanol and PEG-4000 as complexing and co-complexing agents, respectively, were found superior to those prepared without these agents. Apart from its role as a coordinating ligand, tert-butanol activated the Lewis acidic Zn2+ sites for reactions in polyester and polycarbonate formation. Hydrophobicity, micro-mesoporosity, acid strength and the amount of coordinated complexing agent are some of the crucial factors influenced the catalytic activity of DMC complexes.
21st National Symposium on Catalysis (CATSYMP), CSIR Indian Inst Chem Technol, Hyderabad, INDIA, FEB 11-13, 2013
Keywords: aliphatic polycarbonate; CO2 utilization; Double-metal cyanide complex; heterogeneous catalysis; hyperbranched polyester

Synthesis of fatty monoester lubricant base oil catalyzed by Fe-Zn double-metal cyanide complex - Raut, Ravindra K.; Shaikh, Mehejabeen; Darbha, Srinivas (Journal of Chemical Sciences, 2014)
Fatty monoester lubricant base oils as high as 96.7 mol% were prepared by reacting methyl oleate with long-chain alcohols viz., 2-ethyl-1-hexanol (C-8-OH), 1-decanol (C10OH) and 1-dodecanol (C12OH) in the presence of a solid Fe-Zn double-metal cyanide (DMC) complex catalyst. Unlike many other acid catalysts, DMC doesn't produce undesired ether side products. The catalyst was reusable in four recycling experiments with little loss in catalytic activity and ester yield. The long-chain esters prepared in the study have the desired physical properties for their application as lubricant base oils.
Keywords: Fatty monoester; Fe-Zn double-metal cyanide (DMC) catalyst; lubricant base oil; transesterification

Selective aerobic oxidation of alcohols over Au-Pd/sodium titanate nanotubes - Nepak, Devadutta; Darbha, Srinivas (Catalysis Communications, 2015)
catalytic application of Au-Pd nanoparticles supported on sodium titanate nanotubes (NaTNTs) for liquid-phase aerobic oxidation of alcohols is reported, for the first time. This reaction occurs at 80-120 degrees C, 1 atm and solvent-/alkali-free conditions yielding the corresponding carbonyls in high selectivity. This catalyst was reusable and found to be more active/selective than the corresponding monometallic Au and Pd catalysts and Au-Pd/TiO2. Higher dispersion, smaller particle size and higher amount of electron density at gold are the causes for the superior activity of Au-Pd/NaTNT catalyst. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: aerobic oxidation; Alcohol; Bimetallic Au-Pd catalyst; Sodium titanate nanotubes; TiO2

Structure-induced catalytic activity of Co-Zn double-metal cyanide complexes for terpolymerization of propylene oxide, cyclohexene oxide and CO2 - Sebastian, Joby; Darbha, Srinivas (RSC Advances, 2015)
The application of Co-Zn double-metal cyanide (DMC) complexes as catalysts for selective terpolymerization of propylene oxide, cyclohexene oxide and CO2 producing polycarbonates is reported for the first time. DMC complexes were prepared with and without using a co-complexing agent. The catalyst with monoclinic/rhombohedral crystal structure and strong Lewis acidity, prepared without using a co-complexing agent showed higher initial activity than that with a cubic structure prepared using a co-complexing agent. Interestingly, no induction period in the terpolymerization reaction was observed. The terpolymer has 75.5 mol% of carbonate fraction in its composition and an average molecular weight of 22 700 and polydispersity index of 2.97. It is characterized by a T-g of 55 degrees C. This structure-induced catalytic activity of DMC can open up new avenues for its applications in other reactions. The influence of process parameters on the catalytic activity of DMC was investigated.

Catalytic decarboxylation of non-edible oils over three-dimensional, mesoporous silica-supported Pd - Raut, Ravindra; Banakar, Vikram V.; Darbha, Srinivas (Journal of Molecular Catalysis A-Chemical, 2016)
Deoxygenation of fatty acids (oleic and stearic acids) and non-edible oil (jatropha oil) over Pd(1-5 wt%) supported on two structurally different, three-dimensional, mesoporous silica (SBA-12 and SBA-16) catalysts was investigated. Pd/SBA-16 (cubic mesoporous structure with space group Im (3) over barm) showed higher catalytic activity than Pd/SBA-12 (hexagonal mesoporous structure with space group p6(3)/mmc). The influence of reaction parameters like temperature, H-2 pressure and Pd content as well as the nature of the feedstock on catalytic activity and product selectivity was studied. A temperature of above 320 degrees C, reaction time of 5 h and Pd content (on silica surface) of 3 wt% enabled complete conversion of the fatty compounds into diesel-range hydrocarbons. Deoxygenation proceeded through hydrodeoxygenation and decarboxylation mechanisms when a saturated (stearic) acid was used as a feed while it advanced mainly through decarboxylation route when an unsaturated (oleic) acid was employed. Higher surface hydrophobicity and smaller size particles of Pd are the possible causes for the superior catalytic activity of Pd/SBA-16. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Biofuel; Deoxygenation; Diesel-range hydrocarbons; Mesoporous silica; Supported palladium; Vegetable oil

Direct synthesis of dimethyl carbonate from CO2 and methanol over CeO2 catalysts of different morphologies - Unnikrishnan, P.; Darbha, Srinivas (Journal of Chemical Sciences, 2016)
The direct synthesis of dimethyl carbonate (DMC) from carbon dioxide (CO2) and methanol is an attractive approach towards conversion of the greenhouse gas - CO2 into value-added chemicals and fuels. Ceria (CeO2) catalyzes this reaction. But the conversion efficiency of CeO2 is enhanced when the byproduct water in the reaction medium is separated by employing trapping agents like 2-cyanopyridine (2-CP). In this work, the influence of morphology of CeO2 on the direct synthesis of DMC in presence of 2-CP is reported. CeO2 catalysts of cube, rod, spindle and irregular morphology (Ce - C, Ce - R, Ce - S and Ce - N, respectively) were prepared, characterized and studied as catalysts in the said reaction conducted in a batch mode. Among all, Ce - S shows superior catalytic performance with nearly 100 mol% of DMC selectivity. Catalytic activity correlates with the concentration of acid and base sites of medium strength as well as defect sites. Ce - S has an optimum number of these active sites and thereby shows superior catalytic performance.
Keywords: acid-base catalysis; ceria; CO2 utilization; Dimethyl carbonate; influence of morphology

Promotional effect of WOx in Pt-WOx/AlPO4-5 catalyzed deoxygenation of fatty acids - Janampelli, Sagar; Darbha, Srinivas (ChemistrySelect, 2017)
WOx promoted Pt/AlPO4-5 catalysts with varying Pt and W contents were prepared by wet-impregnation method and characterized. Catalysts with Pt to W weight ratio of 1: 2 exhibited higher catalytic performance than the other compositions in deoxygenation of oleic acid (OA). WOx enhanced significantly the catalytic activity of Pt and enabled quantitative conversion of OA to linear alkanes (predominantly C-18/C-17) at a temperature as low as 280 degrees C. It changed the reaction pathway from decarbonylation/ decarboxylation (DCO for Pt/AlPO4-5) to hydrodeoxygenation (HDO for Pt-WOx/AlPO4-5). It affected the particle size and redox behaviour of Pt. The enhanced H-spill over (by 14.8%) and presence of strong acid sites (300 - 500 degrees C) are the cause for the high activity of Pt-WOx/AlPO4-5 catalysts even at lower temperatures. Partially reduced WOx activates OA and leads to the HDO product (C-18). In the absence of WOx, Lewis acid sites of the support activate OA through the C=O group and Pt facilitates C-C cleavage and formation of DCO product (C-17).
Keywords: biofuels; Deoxygenation; Fatty acids; Green Diesel; Hydrocarbons

Direct synthesis of diethyl carbonate from ethanol and carbon dioxide over ceria catalysts - Giram, Ganesh G.; Bokade, Vijay V.; Darbha, Srinivas (New Journal Of Chemistry, 2018)
Direct synthesis of diethyl carbonate (DEC) by carboxylation of ethanol with CO2 was investigated over ceria catalysts. 2-Cyanopyridine (2-CP) was used for trapping water formed in the reaction and to shift the equilibrium towards the product side. An optimal dependence (volcanic plot) of the catalytic activity on the acidity/basicity molar ratio was observed. Neat ceria (procured from Daiichi Kigenso Kagaku Kogyo Co. Ltd, Japan) showed higher catalytic activity than metal incorporated ceria catalysts. CeO2 had the right kind of acidity/basicity ratio to activate ethanol and CO2 simultaneously, yielding DEC. The catalyst was reusable. The yield of DEC obtained in this study using the commercial catalyst was higher than that reported by others using ceria catalysts prepared by other methods. Under optimum conditions (ethanol:2-CP molar ratio = 2:1, catalyst = 2.17 wt% with respect to ethanol, CO2 pressure = 40 bar, reaction temperature = 150 degrees C and reaction time = 3 h) in a batch reaction, a DEC yield as high as 45 mol% (i.e., 38.7 mmol mmol(-1) of CeO2) was obtained.

Effect of support on the catalytic activity of WOx promoted Pt in green diesel production - Janampelli, Sagar; Darbha, Srinivas (Molecular Catalysis, 2018)
Platinum and WOx-promoted platinum supported on SiO2-Al2O3, Al2O3, AlPO4-5 and ZrO2 catalysts were prepared by wet impregnation method and investigated for deoxygenation of oleic acid (OA, a representative fatty acid) producing diesel-range hydrocarbons. Support and WOx influenced the textural, electronic and catalytic properties of Pt. WOx promoted the deoxygenation activity through hydrodeoxygenation pathway. Structure-activity correlations revealed that metallicity of Pt and acidity of the catalyst are crucial in determining the catalytic performance and product selectivity. Among the catalysts tested, 4Pt-8WO(x)/ZrO2, having adequate metal dispersion and electron rich Pt (desired for hydrogen splitting), reduced WOx species (W5+;-desired for OA activation) and less amount of strong acid sites (desired to avoid hydrocracking) showed highest catalytic deoxygenation performance (OA conversion = 100 mol% and C18 hydrocarbon selectivity = 89.4% at 260 degrees C and 20 bar H-2 pressure). The study reveals that support plays a crucial role in determining the catalytic performance of platinum. (C) 2017 Elsevier B.V. All rights reserved.

Metal oxide-promoted hydrodeoxygenation activity of platinum in pt-mox/al2o3 catalysts for green diesel production - Janampelli, Sagar; Darbha, Srinivas (Energy & Fuels, 2018)
Catalytic deoxygenation of fatty acids into renewable hydrocarbons (green diesel) was investigated over 4Pt-8MO(x)/Al2O3 (M = Mo, Re, W, and Sn) catalysts prepared by the wet impregnation method. Platinum deposited on MOx-modified gamma-Al2O3 showed higher catalytic hydrodeoxygenation activity than that of the "neat" Pt/Al2O3 catalyst. The promotional effect of metal oxides (MOx) decreased in the following order: MoOx > ReOx > WOx > SnOx. Characterization studies revealed that metal oxides affect the textural and electronic properties of Pt. Supported Pt facilitated the reduction of these metal oxides. Synergy and electronic contact between Pt and MOx determined the catalytic deoxygenation performance. Fatty acid conversion increased with increasing metallic nature (decreasing binding energy) of Pt. Hydrodeoxygenation product selectivity correlated with the extent of metal oxide reduction. Among the catalysts, 4Pt-8MoO(x)/Al2O3 had the optimum dispersion, electron-rich Pt, and reduced Mo5+ species, enabling quantitative conversion of oleic acid with 93.5% octadecane selectivity at a temperature as low as 220 degrees C and 20 bar hydrogen pressure. Metal oxide switched the mechanism of deoxygenation from decarbonylation/decarboxylation to hydrodeoxygenation. Fatty acids, methyl oleate, and vegetable oil were deoxygenated with equal efficiency over this catalyst. Catalysts were reusable in recycling studies only at higher temperature (320 degrees C) and not at lower temperature (260 degrees C), perhaps due to strong sticking of reactant molecules at lower temperature on the catalyst surface than at higher temperature.

Highly efficient Pt-MoOx/ZrO2 catalyst for green diesel production - Janampelli, Sagar; Darbha, Srinivas (Catalysis Communications, 2019)
Bimetallic Pt-MoOx supported on ZrO2 exhibits higher catalytic activity than known catalysts for converting fatty acids into green diesel at as low as 200 degrees C. A change in selectivity from decarboxylation/decarbonylation to hydrodeoxygenation and enhancement in the deoxygenation activity of Pt were observed when MoOx was also present in the catalyst composition. In X-ray photoelectron spectra, Pt 4f lines of 4Pt-8MoO(x)/ZrO2 occurred at lower binding energies than those for 4Pt/ZrO2. Part of Mo was reduced from +6 to +5 oxidation state in the presence of Pt. There seems to exist some electronic interaction between the support and metal, making 4Pt-8MoO(x)/ZrO2 a highly efficient and selective deoxygenation catalyst.
Keywords: Bimetallic catalyst; Biofuel; Deoxygenation of fatty acids; Green Diesel; Hydrocarbons; Supported platinum catalyst

Hydrodeoxygenation of vegetable oils and fatty acids over different group VIII metal catalysts for producing biofuels - Janampelli, Sagar; Darbha, Srinivas (Catalysis Surveys From Asia, 2019)
Energy security and environment protection are two important aspects of sustainable development. Biofuels are renewable and carbon neutral. They are suitable replacement for conventional fossil derived transport fuels. Their use leads to sustainable development. Among several technological options, catalytic hydrodeoxygenation of vegetable oils leading to diesel-range hydrocarbons is the most attractive approach for producing biofuels. The green diesel, thus produced, could be blended with petro-diesel or used as standalone fuel in the conventional diesel engines. Our research group has been active in developing efficient solid catalysts for hydroprocessing of vegetable oils. This account presents some of our efforts using supported group VIII metals and the importance of electronic contact between metal and support on the catalytic activity and hydrodeoxygenation selectivity in hydroprocessing of vegetable oils.
Keywords: biofuels; Catalysis over group VIII metals; Deoxygenation; Hydroprocessing; Renewable diesel

Catalytic conversion of HMF into ethyl levulinate - a biofuel over hierarchical zeolites - Chithra, P. A.; Darbha, Srinivas (Catalysis Communications, 2020)
Catalytic conversion of 5-hydroxymethyl-2-furfuraldehyde (HMF, a biomass-derived platform chemical) into ethyl levulinate (EL) is an attractive approach for producing renewable transport fuels for mitigating global warming. We report here the application of hierarchical zeolites (DZSM-5 and MZSM-5 synthesized by desilication and mesoporous templating approaches, respectively) as solid acid catalysts for this transformation. Hierarchical structure of these zeolites was confirmed by X-ray diffraction, nitrogen-physisorption and electron microscopy, and acidity was determined by temperature-programmed desorption of ammonia. HMF conversion of 94.2% with EL selectivity of 90.8% was achieved over the MZSM-5 catalyst. Acidity, pore size and surface properties affected the catalytic activity.
Keywords: 5-Hydroxymethyl-2-furfuraldehyde (HMF); Biofuel; ethyl levulinate; Hierarchical zeolite; ZSM-5

Selective, bifunctional Cu-WOx/Al2O3 catalyst for hydrodeoxygenation of fatty acids - Janampelli, Sagar; Sethia, Govind; Darbha, Srinivas (Catalysis Science & Technology, 2020)
Selective hydrodeoxygenation of oleic acid (OA; in a batch reactor, at 300 degrees C, 30 bar H-2 pressure, reaction time of 1 h and reactant-to-catalyst weight ratio of 2 g OA/0.2 g) forming n-octadecane in yields as high as 93% over a non-noble metal, sulfur-free, bimetallic Cu-WOx/Al2O3 catalyst is reported for the first time. Several Cu-WOx/Al2O3 compositions were prepared by a sequential wet-impregnation method and evaluated. A catalyst with 10 wt% Cu and 4 wt% W enabled the highest activity and selectivity. Upon adding WOx, the amount of moderate and strong acid sites increased and more Cu in the catalyst was in reduced electron-rich metallic (Cu-0) state. The crystallite size and dispersion of Cu were little affected. WOx promoted the fatty acid hydrodeoxygenation activity of Cu. While a monometallic Cu catalyst (10Cu/Al2O3) yielded n-octadecane and n-heptadecane along with high amounts of intermediate octadecanol and octadecanal products, the bimetallic catalyst (10Cu-4WO(x)/Al2O3) gave mainly n-octadecane. Acidity and the high amount of reduced Cu-0 species are responsible for the high catalytic hydrodeoxygenation performance of this bimetallic catalyst.

Solid catalysts for conversion of furfural and its derivatives to alkanediols - Enjamuri, Nagasuresh; Darbha, Srinivas (Catalysis Reviews-Science and Engineering, 2020)
Alkanediols with five and six carbon atoms (1,2- & 1,5-pentanediols and 1,2- & 1,6-hexanediols, respectively) are an important class of industrial chemicals having wide application. Their production from lignocellulosic biomass-derived furfural and its derivatives using solid catalysts is a sustainable and attractive approach. Several bifunctional catalysts with metal (for hydrogenation/hydrogenolysis) and acid/base (for ring opening) functionalities have been reported. Effective and selective conversion of furfurals to a desired diol is still a challenge. This review discusses the recent advances in catalyst development for pentane- and hexanediols. The reaction pathways, active sites, and possible reaction mechanisms over the solid catalysts are discussed. A comparative catalytic activity data of the known catalysts are reported.
Keywords: 5-hydroxymethylfurfural (HMF); Alkanediol; furfural (FAL); hexanediol; pentanediol; solid catalyst

Advances in solid catalysts for selective hydrogenolysis of glycerol to 1,3-propanediol - Bhowmik, Susmita; Darbha, Srinivas (Catalysis Reviews-Science and Engineering, 2021)
Glycerol is one of the top 12 platform chemicals obtained from biomass. Its surplus availability as a by-product of biodiesel, fat-splitting and soap manufacturing industries and affordable price lends significant opportunity for its valorization, using solid catalysts, into propanediols (PDOs), particularly to 1,3-propanediol (1,3-PDO), by selective hydrogenolysis. 1,3-PDO is an important chemical with wide applications including that as a precursor in polymers manufacturing. However, the synthesis of 1,3-PDO by selective cleavage of the secondary C-O bond of glycerol in the presence of hydrogen (instead of the primary C-O bond yielding 1,2-PDO) is highly challenging. Of late, supported Pt and Ir catalysts in combination with a reducible oxide (WO(x)or ReOx) were found selective for 1,3-PDO formation. Support, metals composition and additives (co-added metals) affect the performance of these catalysts. Detailed investigations revealed that metal dispersion, electronic connectivity between metal and metal oxide/support, hydrogen activation/spillover and Bronsted acidity are some parameters that influence the activity and selectivity of these bi-functional, metal-metal oxide catalysts. This review summarizes the latest advances in these solid catalysts for selective hydrogenolysis of glycerol to 1,3-PDO, a monomer for advanced polymers.
Keywords: 1; 3-Propanediol; bifunctional metal-metal oxide catalyst; biomass valorization; Glycerol; Hydrogenolysis

Hydrogenolysis of glycerol in an aqueous medium over Pt/WO3/zirconium phosphate catalysts studied by H-1 NMR spectroscopy - Bhowmik, Susmita; Enjamuri, Nagasuresh; Darbha, Srinivas (New Journal of Chemistry, 2021)
Bifunctional Pt/WO3/zirconium phosphate catalyzes the liquid-phase hydrogenolysis of glycerol in an aqueous medium. H-1 NMR spectroscopy (solvent suppression pulse program) is employed to monitor this reaction. Propanediols (1,3 + 1,2-PDO) formed as the major product along with propanols (1- and 2-POs) as the minor product. A synergistic enhancement in glycerol conversion and selectivity to 1,3-PDO was observed when both Pt and WO3 were present in the catalyst. A volcano-shape variation of catalytic activity with W content was observed. A catalyst with 8 wt% W and 1 wt% Pt exhibited the highest selective hydrogenolysis performance (glycerol conversion = 92.3% and total PDOs selectivity = 45.9% and 1,3-PDO selectivity = 20.8% at 200 degrees C). Dispersed Pt in contact with polytungstate-type WO3 species was found to be the active catalytic site. H-1 NMR spectroscopy is demonstrated as an attractive technique to quantify the products of a glycerol hydrogenolysis reaction.

Selective deoxygenation of fatty acids to fuel-range hydrocarbons over Pt-MOx/ZrO2 (M = Mo and W) catalysts - Janampelli, Sagar; Darbha, Srinivas (Catalysis Today, 2021)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">A comparative catalytic activity study of Pt-MoO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">x<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">/ZrO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> and Pt-WO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">x<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">/ZrO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> for deoxygenation of oleic acid (OA) forming fuel-range, linear hydrocarbons is reported. These catalysts (with 4 wt% Pt and 8 wt% Mo or W) were prepared by a sequential wet-impregnation method and characterized for the structural and electronic properties. Pt-MoO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">x<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">/ZrO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> showed higher catalytic activity than Pt-WO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">x<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">/ZrO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">. Hydrodeoxygenation was the selective pathway over these bifunctional catalysts yielding n-octadecane. High conversion of OA was achieved at 200 °C itself. On the contrary, monometallic Pt/ZrO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> was weakly active. It was selective mainly toward decarboxylation/decarbonylation producing n-heptadecane. Higher amounts of Pt and metal oxide in reduced forms are responsible for the high hydrodeoxygenation activity and selectivity of these reusable, bimetallic catalysts.

C-O hydrogenolysis of C3-C4 polyols selectively to terminal diols over Pt/W/SBA-15 catalysts - Bhowmik, Susmita; Enjamuri, Nagasuresh; Marimuthu, Banu; Darbha, Srinivas (Catalysts, 2022)
Pt/W/SBA-15 catalysts (with Pt-loading = 0.5-4 wt% and W-loading = 1 wt%) prepared by the sequential impregnation method were evaluated for selective C-O cleavage of erythritol and glycerol in an aqueous medium. The Pt and W particles dispersed on SBA-15 approached close proximity at higher Pt loadings and afforded synergistic enhancement in C-O hydrogenolysis activity/selectivity. 1,4-Butanediol yields of 30.9% (at 190 degrees C, 50 bar H-2 and 24 h) and 1,3-propanediol yields of 34.4% (at 190 degrees C, 50 bar H-2 and 12 h of reaction) were obtained over these catalysts. Pt nanoparticles (facilitating dissociative H-2 adsorption and spillover) and W (present as acidic oligomeric WOx species; activating and coordinating the polyol via 1 degrees-OH group) worked in tandem for the selective hydrogenolysis of polyols yielding terminal diols of industrial demand.
Keywords: diol; Erythritol; Glycerol; Hydrodeoxygenation; Pt; SBA-15; W

Insights into active tungsten species on Pt/W/SBA-15 catalysts for selective hydrodeoxygenation of glycerol to 1,3-propanediol - Bhowmik, Susmita; Enjamuri, Nagasuresh; Sethia, Govind; Akula, Venugopal; Marimuthu, Banu; Darbha, Srinivas (Molecular Catalysis, 2022)
Diols are important class of industrial chemicals. Their synthesis from bio-resources (instead from fossil feed-stocks) is sustainable. In this study, we probed active tungsten species on Pt/W/SBA-15 catalysts for selective synthesis of 1,3-propanediol (1,3-PDO) from aqueous glycerol through a liquid-phase hydrodeoxygenation re-action. A synergistic enhancement in glycerol conversion and 1,3-PDO selectivity was observed when both Pt and W were present on the catalyst. A volcano-shape variation followed with a gradual increase in glycerol conversion and 1,3-PDO yield with W-loading (0.25-15 wt%) was observed. Pt dispersion and acidity of the catalyst dis-played similar variations with the W-loading confirming their critical role in the reaction. Structure-function relationships inferred that oligomeric WOx with moderate Bro center dot nsted acidity (predominant at 1 wt% W-loading) in contact with dispersed Pt are the active species for 1,3-PDO formation and crystalline WO3 with strong Bro center dot nsted acidity (prevalent above 4 wt% W-loading) in association with Pt nanoparticles lead to 1-propanol formation.
Keywords: 3-Propanediol; Active sites; Glycerol; Hydrodeoxygenation; Hydrogenolysis; Supported Pt-WO x

Promoting effect of titanium on C-O hydrogenolysis of erythritol to 1,4-butanediol over Pt/W/Ti-SBA-15 catalysts - Bhowmik, Susmita; Akula, Venugopal; Sethia, Govind; Marimuthu, Banu; Darbha, Srinivas (Applied Catalysis A-General, 2023)
The C-O hydrogenolysis of erythritol was investigated using Pt/W/Ti-SBA-15 catalysts (4 wt% Pt, 1 wt% W and Si/Ti molar ratio = 50, 33, 20 and 10). Ti-incorporation enhanced the hydrogenolysis activity and the yield of 1,4-butanediol (1,4-BDO). A catalyst with Si/Ti = 20 afforded erythritol conversion of 94 mol% with 1,4-BDO yield of 32.6 mol% and total BDOs yield of 51.7 mol% at 190 degrees C, 50 bar H2 and 12 h. For the catalyst with no titanium (Pt/W/SBA-15), a double the time was required to achieve such yield. There observed electronic connectivity amongst Ti, Pt and W. For the catalyst with Si/Ti = 20, a greater amount of interfacial Pt-O-W(Ti) sites with Pt in + 2 oxidation state was present. The enhanced catalytic performance of these catalysts was corresponded to dispersed Pt (that facilitate hydrogen activation and spillover) and acidic interfacial Pt-O-W sites (that promote the adsorption and hydrogenolysis of erythritol to diols).
Keywords: Biomass conversion; Erythritol; Hydrogenolysis; Polyols; Promotional effect of Ti; Terminal diol; Ti-SBA-15-supported Pt/W catalysts

Advances in catalytic conversion of lignocellulosic biomass to ethylene glycol - Enjamuri, Nagasuresh; Darbha, Srinivas (Catalysis Reviews-Science and Engineering, 2024)
Ethylene glycol (EG) is an industrial chemical with multiple applications in polymers, anti-freeze agents, coolants, desiccants and de-icing fluids. It is prepared mainly from fossil feedstock resources. However, its manufacture from renewable sources like lignocellulosic biomass is attractive from the view points of carbon-neutrality and environmental benefits. A few industries have already ventured or committed to produce biomass-derived EG (bio-EG) on a pilot to demonstration scale. At present bio-EG is more expensive than the EG made from fossil resources. Advances are happening in developing more efficient and selective catalysts for the direct conversion of raw biomass and its hydrolysis products (cellulose and glucose) into bio-EG. This review presents the recent advances in catalysts for producing bio-EG.
Keywords: 2-diol; biomass to chemicals; ethane-1; Hydrogenolysis; Lignocellulose; Monoethylene glycol; solid catalyst